Development and utilization of peptide-based quorum sensing modulators in Gram-positive bacteria. Issue 37 (11th September 2020) - McBrayer, Dominic N.; Cameron, Crissey D.; Tal-Gan, Yftah
Abstract : This review discusses the development of peptide-based quorum sensing modulators and their use as potential therapeutics. Abstract : Quorum sensing (QS) is a mechanism by which bacteria regulate cell density-dependent group behaviors. Gram-positive bacteria generally rely on auto-inducing peptide (AIP)-based QS signaling to regulate their group behaviors. To develop synthetic modulators of these behaviors, the natural peptide needs to be identified and its structure–activity relationships (SARs) with its cognate receptor (either membrane-bound or cytosolic) need to be understood. SAR information allows for the rational design of peptides or peptide mimics with enhanced characteristics, which in turn can be utilized in studies to understand species-specific QS mechanisms and as lead scaffolds for the development of therapeutic candidates that target QS. In this review, we discuss recent work associated with the approaches used towards forwarding each of these steps in Gram-positive bacteria, with a focus on species that have received less attention.